FOCAL MOTOR SEIZURES WITH HYPERKINETIC AUTOMATISMS IN PEDIATRIC PRACTICE - K. Yu. Mukhin (Эпилепсия и пароксизмальные состояния, 2016)
Abstract: focal motor seizures with hyperkinetic automatisms (FSHA) – seizures with involves predominantly proximal limb or axial muscles producing irregular sequential ballistic movements. In our study we revealed FSHA in 1.5% of all cases of epilepsy with onset of seizures before 18 years old (n=1261). Onset of epilepsy with FSHA varied widely – from 9 month to 18 years of life; middle age of onset was 6.3 years ± 5.9 years. FSHA occurred in combination with 8 different types of seizures. Remission was achieved in 42.1% cases of epilepsy, associated with FSHA. Reduction of seizure frequency ≥50% on antiepileptic treatment was achieved in 42.1% of the patients.